Catalytic Hydrogenation of Carbon Dioxide to Fuels - Yan, Xuecheng; Guo, Han; Yang, Dongjiang; Qiu, Shilun; Yao, Xiangdong (Current Organic Chemistry, 2014)
Energy and environmental issues are the focus of our concerns, which have become increasingly important nowadays. There is no denying that carbon dioxide is the culprit of greenhouse effect due to the excessive consumption of fossil-based fuels in the past centuries. In order to mitigate the effect of CO2 on the environment and to realize the goal of sustainable development, it is of great importance to convert it into fuels. In this review, the main points will be concentrated on recent advances in designing efficient catalysts for the hydrogenation of CO2 to valuable fuels, such as hydrogenation of CO2 to methanol, conversion of CO2 to CO via reverse water-gas shift reaction and production of hydrocarbons through Fischer-Tropsch synthesis. Meanwhile, some key obstacles that need to be cracked to speed up the industrialization of CO2 fixation will be discussed as well.
Keywords: Fischer-Tropsch synthesis